PENERAPAN ASAS KESEIMBANGAN DALAM PERJANJIAN PENGIKATAN JUAL BELI TANAH DAN BANGUNAN RUMAH PADA PERUMAHAN PALM RESIDENCE KOTA SURABAYA (Analisis Hukum Terhadap Tahap Pra dan Kontraktual Penyusunan Kontrak Baku Sehubungan dengan Keberadaan Klausula Eksonerasi) - , Ratna Puspitasari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is aimed at identifying and assessing the implementation of the principle of equilibrium, particularly in the pre and contractual phase of the making of standard contract of the agreement to sale and purchase for land and residential building, identifying further the reasons of exoneration clause in the standard contracts which are categorized as a violation of the principle of equilibrium, and identifying the arising legal consequences for the party who made the contract and the contract itself if the principle of equilibrium in the standard contract is violated. This research belongs to a normative juridical research because the target of this research is law or norm which includes the principles of law in the extent of vertical synchronization. As a normative juridical research, the emphasis to answer the problems was in the library research. In order to asses, it was not sufficient to understand the principles of law textually, but it also needed contextual understanding. Accordingly, a field research was still required to support the library research. Both data were analyzed qualitatively by using four approaches at the same time, namely statue approach, case approach, comparative approach, and conceptual approach so as to generate descriptive analytical data. Based on the research results, First, the principle of equilibrium had not been implemented thoroughly in the pre and contractual phase of the making of standard contracts of the sale and purchase agreement because some mutually correlated elements of the principle of freedom of contract and good faith were not fulfilled to meet the equilibrium when the contract was made. Second, the exoneration clause in accordance with Article 18 of Consumer Protection Law was categorized as a violation of the principle of equilibrium because the substance contained transferring, eliminating responsibility, and expanding the meaning of force majeure which indicated the disproportionality of the parties through the result of the making of the contract which was interpreted with bad faith. Third, the legal consequences of the violation of the principles of equilibrium in the standard contract were the emergence of disadvantages including: short-term relationship, potential lawsuit from consumers who suffered from losses, imposition of criminal sanctions and/or administrative sanctions, loss of customers both morally and materially, leading to unconscionable contract, opening the opportunities for abuse, the agreement either partially or entirely was potential to be legally null and void depending on whether there was a clause of the severability of provisions